Maid to order in Hong Kong stories of Filipina workers - Constable, Nicole (Ithaca Cornell University Press, 1997)
As middle-class Chinese women have entered the Hong Kong work force in unprecedented numbers over the past two decades, the demand for foreign domestic workers has soared. Approximately 150,000 individuals now serve on two-year contracts, and the vast majority are women from the Philippines. Nicole Constable tells their story. Interweaving her analysis with anecdotal evidence collected in interviews with individual domestic workers, she shows how power is expressed in the day-to-day lives of Filipina domestic workers. Filipina guest workers flooding into Hong Kong are implicitly compared to Chinese domestic workers and found wanting. Local, cultural, and historical factors influence their treatment, as do preconceptions about gender, ethnicity, and class. Constable explains how domestic workers are controlled and disciplined by employment agencies, by employers themselves, and by state policies such as the rule against working for more than one employer. The forms of discipline range from physical abuse to intrusive regulations including restrictions on hair length and the prohibition of lipstick. Filipina workers resist oppression through legal action and political protests, through their use of household or public space, and through less confrontational means such as jokes and pranks. Some find real satisfaction in their work, Constable says, and she warns against any simplistic characterization of domestic workers as either empowered or oppressed, class-conscious or unaware.
Foreign and domestic in Hong Kong -- Global themes and local patterns -- Superior servants -- The trade in workers -- Household rules and relations -- Disciplined migrants, docile workers -- Resistance and protest -- Docility and self-discipline -- Pleasure and power.
Includes bibliographical references (pages [225]-230) and index.
PI-8283 donated by Department of Global Development Cornell University Ithaca.
Keywords: Foreign workers, Filipino -- China -- Hong Kong; Filipinos -- Employment -- China -- Hong Kong